Laparoscopic Pyelolithotomy for Management of Complete Staghorn Stone of An Ectopic Pelvic Kidney - Soltani, Mohammad Hossein; Hamedanchi, Sepehr; Shakiba, Behnam; Hoshyar, Hassan (Urology Journal, 2018)
A 40-year-old man was referred to our urology clinic due to vague abdominal pain and hematuria. Computed tomography (CT) without contrast material visualized an ectopic kidney in the left iliac fossa with a complete staghorn stone. Under general anesthesia, operation was done in supine position with a gentle lateral elevation on the right side. The surgeon stands on the right side of the patient. First, a 12 mm port was inserted at the umbilicus using the Hasson technique. After creation of pneumoperitoneum, operation was done by three 5 mm trocars were arranges as paraumbilical, the point between umbilicus and inguinal canal at left and right side. A vertical pyelotomy incision was made over the anterior pelvic wall and then extended to a cross figure. The stone extracted intact with a laparoscopic stone grasper and placed in endobag. A short double J stent was placed via the pyelotomy incision and renal pelvis was closed using continuous 4.0 vicryl sutures. He was discharged from hospital after 3 days without any complication.